POSITIVE LEGAL EDUCATION TO CREATE A RELIGIOUS AND PRODUCTIVE YOUTH GENERATION EDUKASI HUKUM POSITIF UNTUK MEWUJUDKAN GENERASI MUDA YANG TANGGUH DAN PRODUKTIF - Fatmawati; Hardiyanto Toni; Ismiyanto; Firstnandiar Glica Aini Suniaprily; Hadi Mahmud (Jurnal Pengabdian Kepada Masyarakat "SIDOLUHUR", 2024)
The dynamics and potential for legal problems that occur in society are very complex, as is the case when the community thinks that criminal law is justified as expensive, verbose, long- winded, corruptive, the public does not seem to believe in criminal law as a means of law, so that chaos occurs far from the goal of order and order, community servise activities the people of Bentakan Village, Baki District, Sukoharjo Regency, Central Java, in the form of Legal Counseling is carried out to provide information and legal knowledge related to the importance of information about positive law education, activities to provide assistance to the Bentakan Village community to help when the community wants to carry out legal consultations. This legal counseling helps the community to know and understand their needs and it is hoped that after this counseling, the people of Bentakan Village can understand criminal acts and know the function of criminal law so that order and order can occur in everyday society.